Correlation between diarrhoea associated SNPs and pre-weaning growth rate in Landlly piglets - DARJI, MAYANK; SAHOO, NIHAR RANJAN; MOURYA, RAJVEER; SANTHOSH, AMEYA; SAINI, B L; KUMAR, PUSHPENDRA; GAUR, G K; QURESHI, SALAUDDIN; KUMAR, AMIT; SONWANE, ARVIND (The Indian Journal of Animal Sciences, 2025)
The present study was aimed to investigate the relationship between diarrhoea-associated polymorphisms and pre-weaning growth rates in an organized Landlly herd. A total of 250 piglets were genotyped for 10 shortlisted SNPs and assessed for pre-weaning growth rates, with body weights recorded from birth to the 6th week of age. Seven out of the 10 SNPs were found to be polymorphic in the target population, with the MUC 4-g.8227 G>C locus significantly affecting growth rates of the 2nd to 4th week piglets whereas, the MUC 20-g.191 affected growth rates at the 4th week of age. These findings suggest that the g.8227C>G and g.191C>T SNP polymorphisms are associated with both growth performance and diarrhoea in piglets, recommending that a balanced approach should be maintained between health status and growth performance in piglet selection programs.